Hydrogel fever cooling patch and preparation method thereof

By adopting a multi-layer structure hydrogel anti-heat patch and using hydrogel layers and matrix layers made of raw materials such as wrinkled carrageenanth, the adhesion, stability and cooling performance of the existing anti-heat patch are solved. The problem has achieved more efficient and lasting anti-heat effect.

CN119454332AInactive Publication Date: 2025-02-18ZHUHAI GUOJIA NEW MATERIAL

Patent Information

Application Number
CN202411496965.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The adhesion, stability, moisture content, cooling performance and durability of existing anti-heat patches are not ideal, which limits the use and effect of the product.

Method used

The hydrogel layer and matrix layer are made of raw materials such as wrinkled carrageenan, potassium chloride, calcium chloride, thickener, moisturizing agent, preservative, pomelo capsule extract and benzedonium The layer structure anti-heating patch is obtained by static molding.

Benefits of technology

It improves the adhesion, stability, cooling performance and durability of the anti-heat patch, enhances the comfort and safety of the product, and at the same time improves the moisture content to achieve efficient heat reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101506890000081
    Figure BDA0005101506890000081
  • Figure BDA0005101506890000091
    Figure BDA0005101506890000091
Patent Text Reader

Abstract

The invention provides a hydrogel fever cooling patch which comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom, and the hydrogel layer is prepared from the following raw materials in percentage by weight: 0.5-3% of chondrus crispus (CHOWDRUS CRISPUS), 0.1-1% of potassium chloride, 0.1-1% of calcium chloride, 0.5-3% of a thickening agent, 5-30% of a humectant, 0.5-3% of a preservative, 0.4-0.8% of a pomelo sac extract and the balance of water. The sum of the weight percentages of the raw materials is 100%, and the sum of the weight percentages of the raw materials is 100%. The substrate layer is prepared from the following raw materials in percentage by weight: 1-10% of sodium polyacrylate, 0.01-0.5% of a chelating agent, 5-30% of a humectant, 0.1-1% of a cross-linking agent, 0.1-1% of a cross-linking regulator, 0.5-3% of a thickening agent, 0.5-3% of a preservative, 0.1-1% of thermochromic microcapsules and the balance of pure water, and the sum of the weight percentages of the raw materials is 100%. The invention further provides a preparation method of the hydrogel fever cooling patch. The hydrogel fever cooling patch provided by the invention has relatively good adhesiveness, stability, cooling performance and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cooling patch, in particular to a hydrogel cooling patch and a preparation method thereof. Background Art

[0002] Fever, commonly known as fever, is a symptom name. In normal people, the body's heat production and heat dissipation process often maintains a dynamic balance under the control of the body temperature regulation center. When the body is under the action of a heat source or the body temperature center is dysfunctional, the heat production process increases and the heat dissipation cannot increase accordingly or the heat dissipation decreases, resulting in a body temperature ≥37.3℃, which is called fever. When the fever temperature is below 38.5℃, it is a low fever and physical cooling can be used; when the body temperature exceeds 38.5℃, it is advisable to use drug treatment, and physical cooling can also be used to relieve fever symptoms and reduce patient discomfort. Fever patches are common household antipyretic products, which are widely used in fever, summer heat relief, and high-temperature work.

[0003] Most of the existing cooling patches are made of high molecular polymer as the skeleton material, and are mainly divided into: with backing layer type and without backing layer type. The working principle is that the high molecular polymer forms a gel layer with a large amount of liquid water. When used, the heat on the skin surface vaporizes it, takes away the heat and plays a role in reducing the local temperature. The problems of the existing cooling patches are that the adhesion, stability, water content, cooling performance and durability are not ideal, which limits the use and effect of the cooling patch products.

[0004] Patent CN202210272683.0 discloses "a method for manufacturing a sterile polymer hydrogel patch and a sterile polymer hydrogel patch prepared by the method", and its manufacturing method includes: the first step: pretreatment of raw materials; the second step: preparing polymer hydrogel materials; the third step: placing the prepared hydrogel material in a molded roller coating machine for coating and cutting; the fourth step: curing and drying the cut semi-finished products; the fifth step: initial packaging of the cut semi-finished products; the sixth step: sterilizing and analyzing the packaged finished products with ethylene oxide to obtain a sterile antipyretic patch finished product; the raw material pretreated in the first step is polyvinyl alcohol, and the pretreatment is to place the polyvinyl alcohol in a chemical tank and add purified water; the polymer hydrogel material prepared in the second step is: placing the pretreated polyvinyl alcohol solution, adding purified water and triethanolamine in a vacuum mixer, and vacuum stirring; the third step is to coat and cut the prepared polymer hydrogel material; the manufactured sterile polymer hydrogel patch can effectively cool down and reduce fever. The hydrogel patch produced by this patent has poor cooling performance and durability, and its adhesion and stability are also not ideal. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a hydrogel cooling patch, which has good adhesion, stability, cooling performance and durability.

[0006] In order to solve the above technical problems, the technical solution of the present invention is:

[0007] A hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 0.5-3% of Chondrus crispus, 0.1-1% of potassium chloride, 0.1-1% of calcium chloride, 0.5-3% of thickener, 5-30% of moisturizing agent, 0.5-3% of preservative, 0.4-0.8% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 1-10% of sodium polyacrylate, 0.01-0.5% of chelating agent, 5-30% of moisturizing agent, 0.1-1% of crosslinking agent, 0.1-1% of crosslinking regulator, 0.5-3% of thickener, 0.5-3% of preservative, 0.1-1% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%.

[0008] Furthermore, the thickener of the present invention is one or more of Rhodophyta extract, glucomannan, sodium carboxymethyl cellulose or polyvinyl pyrrolidone.

[0009] Furthermore, the moisturizing agent of the present invention is one or more of glycerol, ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol or sorbitol.

[0010] Furthermore, the preservative of the present invention is one or more of phenoxyethanol, ethylhexylglycerin, glyceryl caprylate, caprylhydroxamic acid, p-hydroxyacetophenone or 1,2-hexanediol.

[0011] Furthermore, the grapefruit capsule extract of the present invention is prepared by the following steps:

[0012] The peel, pulp, cyst and seeds of fresh pomelo were separated, the cyst was crushed and sieved to obtain cyst powder, the cyst powder was added into ethanol aqueous solution and soaked for 24 hours, the supernatant was discarded, the residue was added into distilled water and ultrasonically extracted for 20 minutes to obtain an extract, the extract was filtered to obtain a filter residue, the filter residue was washed with deionized water for 3 times, placed in a drying oven to dry to constant weight, taken out, crushed and sieved to obtain a pomelo cyst extract.

[0013] Furthermore, in the preparation steps of the grapefruit capsule extract of the present invention, the particle size of the capsule coating powder is 80 mesh, the volume concentration of the ethanol aqueous solution is 95%, the weight ratio of the capsule coating powder to the ethanol aqueous solution is 1:5, the weight ratio of the residue to distilled water is 1:25, the ultrasonic power during ultrasonic extraction is 400 W, the temperature of the drying oven is 60° C., and the particle size of the grapefruit capsule extract is 80 mesh.

[0014] Furthermore, the chelating agent of the present invention is one or more of disodium EDTA, tetrasodium EDTA or EDTA.

[0015] Furthermore, the cross-linking agent of the present invention is one or more of aluminum glycolate, aluminum hydroxide, aluminum sulfate, calcium sulfate or calcium hydroxide.

[0016] Furthermore, the cross-linking regulator of the present invention is one or more of citric acid, lactic acid or succinic acid.

[0017] Furthermore, the thermochromic microcapsules of the present invention are prepared by the following steps:

[0018] Cholesteryl butyrate, ethyl orthosilicate, hexadecyltrimethylammonium bromide and formamide in a ratio of 9g:7g:1g:100mL were mixed, and the mixture was stirred at 1200r / min for 4 hours to obtain a mixed emulsion; a hydrochloric acid solution with a mass concentration of 15% was dropwise added into the mixed emulsion at a volume ratio of 2:1, and the mixture was stirred at 500r / min for 6 hours and then allowed to stand for 24 hours to obtain a reaction solution; the reaction solution was centrifuged at 1500r / min for 10 minutes to obtain a precipitate; the precipitate was washed 3 times with deionized water, and dried in a drying oven at 60°C to constant weight to obtain thermochromic microcapsules.

[0019] Furthermore, the hydrogel cooling patch of the present invention is of forehead type, nasolabial fold type, eye patch type, lifting type or acupoint type.

[0020] Another technical problem to be solved by the present invention is to provide a method for preparing the hydrogel cooling patch.

[0021] To solve the above technical problems, the technical solution is:

[0022] A method for preparing a hydrogel cooling patch comprises the following steps:

[0023] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at a speed of 100-300 rpm until the mixture is uniform to obtain a hydrogel layer;

[0024] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 100-300rpm until the mixture is uniform to obtain a matrix layer;

[0025] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The hydrogel antipyretic patch provided by the present invention has a backing-free structure, does not feel inconsistent with the application site, and can adapt to a variety of special needs and uses.

[0028] (2) The hydrogel antipyretic patch provided by the present invention has a high water content, and the high water content has a highly effective antipyretic effect.

[0029] (3) The hydrogel antipyretic patch provided by the present invention will not cause changes in skin cell morphology when used continuously for a long time, and has good comfort and safety in use.

[0030] (4) The Chondrus crispa used in the present invention is a moisturizing ingredient extracted from natural seaweed, which can increase the water content and play a moisturizing role, thereby improving the cooling performance of the hydrogel cooling patch. It is also a good flavoring ingredient and can effectively remove sweat odor. In addition, it has good consistency and can improve the adhesion of the hydrogel cooling patch.

[0031] (5) The denatonium benzoate used in the present invention has a very strong bitter taste, which can prevent poisoning incidents caused by accidental ingestion by humans and animals. Adding it as an aversive agent to the hydrogel antipyretic patch can effectively prevent accidental ingestion.

[0032] (6) The present invention extracts the pomelo capsule part of the pomelo by an ultrasonic-assisted solvent extraction method to obtain a pomelo capsule extract, which contains a large amount of fiber and has good water retention and stability. Therefore, it can further improve the stability, cooling performance and durability of the hydrogel cooling patch.

[0033] (7) The thermochromic microcapsules used in the present invention are made of a thermochromic material - cholesteryl butyrate, and can change color as the temperature changes. In addition, the thermochromic material is coated with microcapsule technology, which can effectively improve its stability and prevent leakage. DETAILED DESCRIPTION

[0034] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.

[0035] Example 1

[0036] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 1.5% of Chondrus crissum, 0.5% of potassium chloride, 0.5% of calcium chloride, 1.5% of thickener, 20% of moisturizing agent, 1.5% of preservative, 0.6% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 6% of sodium polyacrylate, 0.25% of chelating agent, 20% of moisturizing agent, 0.6% of crosslinking agent, 0.6% of crosslinking regulator, 1.5% of thickener, 1.5% of preservative, 0.6% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is glucomannan, the moisturizer is glycerin, the preservative is p-hydroxyacetophenone, the chelating agent is disodium EDTA, the cross-linking agent is aluminum glycolate, and the cross-linking regulator is citric acid.

[0037] Grapefruit capsule extract is made by the following steps:

[0038] The peel, pulp, capsule and seeds of fresh pomelo are separated, the capsule is crushed and sieved to obtain capsule powder with a particle size of 80 meshes, the capsule powder is added to an ethanol aqueous solution with a volume concentration of 95% at a weight ratio of 1:5, immersed for 24 hours, and the supernatant is discarded, the residue is added to distilled water at a weight ratio of 1:25, and ultrasonic extraction is performed at 400W ultrasonic power for 20 minutes to obtain an extract, the extract is filtered to obtain a filter residue, the filter residue is washed with deionized water for 3 times, placed in a drying oven at 60°C to dry to constant weight, taken out, crushed and sieved to obtain a pomelo capsule extract with a particle size of 80 meshes.

[0039] Thermochromic microcapsules are made by the following steps:

[0040] Cholesteryl butyrate, ethyl orthosilicate, hexadecyltrimethylammonium bromide and formamide in a ratio of 9g:7g:1g:100mL were mixed, and the mixture was stirred at 1200r / min for 4 hours to obtain a mixed emulsion; a hydrochloric acid solution with a mass concentration of 15% was dropwise added into the mixed emulsion at a volume ratio of 2:1, and the mixture was stirred at 500r / min for 6 hours and then allowed to stand for 24 hours to obtain a reaction solution; the reaction solution was centrifuged at 1500r / min for 10 minutes to obtain a precipitate; the precipitate was washed 3 times with deionized water, and dried in a drying oven at 60°C to constant weight to obtain thermochromic microcapsules.

[0041] The preparation method of Example 1 comprises the following steps:

[0042] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at a speed of 200 rpm until the mixture is uniform to obtain a hydrogel layer;

[0043] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 200 rpm until the mixture is uniform to obtain a matrix layer;

[0044] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0045] Example 2

[0046] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom, wherein the hydrogel layer is made of the following raw materials in weight percentage: 0.5% of Chondrus crispus, 1% of potassium chloride, 1% of calcium chloride, 2% of thickener, 25% of moisturizing agent, 1% of preservative, 0.5% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 1% of sodium polyacrylate, 0.5% of chelating agent, 25% of moisturizing agent, 0.2% of crosslinking agent, 0.2% of crosslinking regulator, 2% of thickener, 1% of preservative, 1% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is the extract of Rhodophyta, the moisturizer is ethylene glycol, the preservative is 1,2-hexanediol, the chelating agent is tetrasodium EDTA, the cross-linking agent is aluminum hydroxide, and the cross-linking regulator is lactic acid.

[0047] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0048] The preparation method of Example 2 comprises the following steps:

[0049] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at 100 rpm until the mixture is uniform to obtain a hydrogel layer;

[0050] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 100 rpm until the mixture is uniform to obtain a matrix layer;

[0051] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0052] Example 3

[0053] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are bonded in sequence from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 3% of Chondrus CRISPUS, 0.1% of potassium chloride, 0.1% of calcium chloride, 3% of thickener, 5% of moisturizing agent, 2% of preservative, 0.7% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 5% of sodium polyacrylate, 0.1% of chelating agent, 5% of moisturizing agent, 0.1% of crosslinking agent, 0.1% of crosslinking regulator, 3% of thickener, 2% of preservative, 0.7% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is sodium carboxymethyl cellulose, the moisturizing agent is propylene glycol, the preservative is phenoxyethanol, the chelating agent is EDTA, the crosslinking agent is aluminum sulfate, and the crosslinking regulator is succinic acid.

[0054] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0055] The preparation method of Example 3 comprises the following steps:

[0056] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at 300 rpm until the mixture is uniform to obtain a hydrogel layer;

[0057] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 300 rpm until the mixture is uniform to obtain a matrix layer;

[0058] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0059] Example 4

[0060] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 1% of Chondrus crissum, 0.8% of potassium chloride, 0.6% of calcium chloride, 0.5% of thickener, 30% of moisturizing agent, 3% of preservative, 0.4% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 4% of sodium polyacrylate, 0.3% of chelating agent, 30% of moisturizing agent, 0.8% of cross-linking agent, 0.8% of cross-linking regulator, 0.5% of thickener, 3% of preservative, 0.4% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is polyvinyl pyrrolidone, the moisturizer is butylene glycol, the preservative is ethylhexylglycerin, the chelating agent is disodium EDTA, the cross-linking agent is calcium sulfate, and the cross-linking regulator is citric acid.

[0061] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0062] The preparation method of Example 4 comprises the following steps:

[0063] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at a speed of 200 rpm until the mixture is uniform to obtain a hydrogel layer;

[0064] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 200 rpm until the mixture is uniform to obtain a matrix layer;

[0065] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0066] Example 5

[0067] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 2% of Chondrus crissum, 0.3% of potassium chloride, 0.4% of calcium chloride, 1% of thickener, 15% of moisturizing agent, 0.5% of preservative, 0.8% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 10% of sodium polyacrylate, 0.4% of chelating agent, 15% of moisturizing agent, 0.5% of crosslinking agent, 0.5% of crosslinking regulator, 1% of thickener, 0.5% of preservative, 0.8% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is sodium carboxymethyl cellulose, the humectant is polyethylene glycol, the preservative is glyceryl caprylate, the chelating agent is EDTA, the cross-linking agent is calcium hydroxide, and the cross-linking regulator is succinic acid.

[0068] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0069] The preparation method of Example 5 comprises the following steps:

[0070] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at 100 rpm until the mixture is uniform to obtain a hydrogel layer;

[0071] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 100 rpm until the mixture is uniform to obtain a matrix layer;

[0072] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0073] Example 6

[0074] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are sequentially bonded from top to bottom. The hydrogel layer is made of the following raw materials in percentage by weight: 2.5% of Chondrus crissum, 0.6% of potassium chloride, 0.8% of calcium chloride, 2.5% of thickener, 10% of moisturizing agent, 2.5% of preservative, 0.5% of grapefruit capsule extract, 0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in percentage by weight: 8% of sodium polyacrylate, 0.01% of chelating agent, 10% of moisturizing agent, 1% of crosslinking agent, 1% of crosslinking regulator, 2.5% of thickener, 2.5% of preservative, 0.6% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%. Among them, the thickener is glucomannan, the moisturizer is sorbitol, the preservative is caprylhydroxamic acid, the chelating agent is tetrasodium EDTA, the cross-linking agent is aluminum glycolate, and the cross-linking regulator is lactic acid.

[0075] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0076] The preparation method of Example 6 comprises the following steps:

[0077] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at 300 rpm until the mixture is uniform to obtain a hydrogel layer;

[0078] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 300 rpm until the mixture is uniform to obtain a matrix layer;

[0079] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0080] Comparative Example 1

[0081] The difference from Example 1 is that the raw materials of the hydrogel layer do not include Chondrus CRISPUS.

[0082] Comparative Example 2

[0083] The difference from Example 1 is that the raw materials of the hydrogel layer do not include the grapefruit capsule extract, and the preparation step of the grapefruit capsule extract is omitted.

[0084] Comparison Example

[0085] In the specific implementation method of patent CN202210272683.0, the parameter values ​​appearing in its manufacturing method are all taken as the middle values ​​of its disclosed numerical range.

[0086] Experimental Example 1: Cooling Performance Test

[0087] Test reference standard / method: Cooling performance experimental method in T / GDMDMA 0021-2022.

[0088] Test instrument: Thermocouple temperature probe.

[0089] Test objects: hydrogel antipyretic patches prepared in Examples 1-6, Comparative Examples 1-2, and the hydrogel patch prepared in the control example.

[0090] Test objective: The temperature drop of the test object after 30 minutes of testing, ΔT1, and the temperature drop of the test object after 2 hours of testing, ΔT2.

[0091] The larger the ΔT1, the better the cooling performance. The larger the ΔT2, the better the durability of the cooling performance. The test results are shown in Table 1:

[0092]

[0093]

[0094] Table 1

[0095] As can be seen from Table 1, ΔT1 and ΔT2 of Examples 1-6 of the present invention are greater than those of the control example, indicating that the present invention has good cooling performance and durability. Some of the raw materials and preparation steps used in Comparative Examples 1-2 are different from those in Example 1. Compared with Example 1, ΔT1 and ΔT2 of Comparative Examples 1 and 2 are reduced, indicating that the Chondrus crispa and grapefruit capsule extracts used in the present invention can improve the cooling performance and durability of the hydrogel antipyretic patch.

[0096] Experimental Example 2: Stability Test

[0097] Test method: Place the cooling patch in an aluminum foil bag, place the aluminum foil bag in an environment of 40±1°C and 65±5% relative humidity for 4 months, and then evaluate the appearance of the cooling patch.

[0098] Test object, target: peeling force of the hydrogel cooling patch prepared in Examples 1-6, Comparative Example 2, and the hydrogel patch prepared in the control example.

[0099] The test results are shown in Table 2:

[0100] Example 1 Soft, no lumps Example 2 Soft, no lumps Example 3 Soft, no lumps Example 4 Soft, no lumps Example 5 Soft, no lumps Example 6 Soft, no lumps Comparative Example 2 The corners are slightly hardened, without lumps Comparison Example A small amount of hardening and caking appeared on the corners

[0101] Table 2

[0102] As can be seen from Table 2, Examples 1-6 of the present invention are all soft and free of lumps after being placed at high temperature for 4 months, indicating that the present invention has good stability. Some of the raw materials and preparation steps used in Comparative Example 2 are different from those in Example 1. Compared with Example 1, the edges and corners of Comparative Example 2 are slightly hardened after being placed at high temperature for 4 months, indicating that the grapefruit capsule extract used in the present invention can improve the stability of the hydrogel antipyretic patch.

[0103] Experimental Example 3: Adhesion Test

[0104] Test reference standard / method: Peel strength test method in YY / T0148-2006.

[0105] Test instrument: Dynamometer.

[0106] Test object, target: peeling force of the hydrogel cooling patch prepared in Examples 1-6, Comparative Example 1, and the hydrogel patch prepared in the control example.

[0107] The higher the peel force, the better the adhesion. The test results are shown in Table 3:

[0108] Peel force(N) Example 1 2.2 Example 2 2.0 Example 3 2.0 Example 4 2.1 Example 5 2.2 Example 6 2.1 Comparative Example 1 1.7 Comparison Example 1.4

[0109] Table 3

[0110] As can be seen from Table 3, the peeling forces of Examples 1-6 of the present invention are all higher than those of the control example, indicating that the present invention has good adhesion. Some of the raw materials and preparation steps used in the comparative example 1 are different from those in the example 1. Compared with the example 1, the peeling force of the comparative example 1 is reduced, indicating that the Chondrus CRISPUS used in the present invention can improve the adhesion of the hydrogel antipyretic patch.

[0111] Example 7

[0112] The hydrogel antipyretic patch comprises a hydrogel layer, a matrix layer and a hydrogel layer which are bonded in sequence from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 3% of Chondrus CRISPUS, 0.1% of potassium chloride, 0.1% of calcium chloride, 3% of thickener, 5% of moisturizing agent, 2% of preservative, 0.7% of grapefruit capsule extract, and the balance is pure water, and the sum of the weight percentages of each raw material is 100%; the matrix layer is made of the following raw materials in weight percentage: 5% of sodium polyacrylate, 0.1% of chelating agent, 5% of moisturizing agent, 0.1% of crosslinking agent, 0.1% of crosslinking regulator, 3% of thickener, 2% of preservative, 0.7% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of each raw material is 100%. Among them, the thickener is sodium carboxymethyl cellulose, the moisturizing agent is propylene glycol, the preservative is phenoxyethanol, the chelating agent is EDTA, the crosslinking agent is aluminum sulfate, and the crosslinking regulator is succinic acid.

[0113] The preparation steps of grapefruit capsule extract and thermochromic microcapsules are the same as those in Example 1.

[0114] The preparation method of Example 7 comprises the following steps:

[0115] S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, and pure water, and stir at 300 rpm until the mixture is uniform to obtain a hydrogel layer;

[0116] S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 300 rpm until the mixture is uniform to obtain a matrix layer;

[0117] S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

[0118] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A hydrogel cooling patch, characterized in that: The invention comprises a hydrogel layer, a matrix layer and a hydrogel layer which are bonded in sequence from top to bottom. The hydrogel layer is made of the following raw materials in weight percentage: 0.5-3% of Chondrus crispus, 0.1-1% of potassium chloride, 0.1-1% of calcium chloride, 0.5-3% of thickener, 5-30% of moisturizing agent, 0.5-3% of preservative, 0.4-0.8% of grapefruit capsule extract, 0-0.002% of denatonium benzoate, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%; the matrix layer is made of the following raw materials in weight percentage: 1-10% of sodium polyacrylate, 0.01-0.5% of chelating agent, 5-30% of moisturizing agent, 0.1-1% of crosslinking agent, 0.1-1% of crosslinking regulator, 0.5-3% of thickener, 0.5-3% of preservative, 0.1-1% of thermochromic microcapsule, and the balance is pure water, and the sum of the weight percentages of the raw materials is 100%.

2. The hydrogel cooling patch according to claim 1, characterized in that: The thickener is one or more of RHODOPHYTA extract, glucomannan, sodium carboxymethyl cellulose or polyvinyl pyrrolidone.

3. The hydrogel cooling patch according to claim 1, characterized in that: The moisturizing agent is one or more of glycerol, ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol or sorbitol.

4. The hydrogel cooling patch according to claim 1, characterized in that: The preservative is one or more of phenoxyethanol, ethylhexylglycerin, glyceryl caprylate, caprylhydroxamic acid, p-hydroxyacetophenone or 1,2-hexanediol.

5. The hydrogel cooling patch according to claim 1, characterized in that: The grapefruit capsule extract is prepared by the following steps: The peel, pulp, cyst and seeds of fresh pomelo were separated, the cyst was crushed and sieved to obtain cyst powder, the cyst powder was added into ethanol aqueous solution and soaked for 24 hours, the supernatant was discarded, the residue was added into distilled water and ultrasonically extracted for 20 minutes to obtain an extract, the extract was filtered to obtain a filter residue, the filter residue was washed with deionized water for 3 times, placed in a drying oven to dry to constant weight, taken out, crushed and sieved to obtain a pomelo cyst extract.

6. The hydrogel cooling patch according to claim 5, characterized in that: In the preparation steps of the pomelo capsule extract, the particle size of the pomelo capsule powder is 80 meshes, the volume concentration of the ethanol aqueous solution is 95%, the weight ratio of the pomelo capsule powder to the ethanol aqueous solution is 1:5, the weight ratio of the residue to distilled water is 1:25, the ultrasonic power during ultrasonic extraction is 400W, the temperature of the drying oven is 60°C, and the particle size of the pomelo capsule extract is 80 meshes.

7. The hydrogel cooling patch according to claim 1, characterized in that: The chelating agent is one or more of disodium EDTA, tetrasodium EDTA or EDTA.

8. The hydrogel cooling patch according to claim 1, characterized in that: The cross-linking agent is one or more of aluminum glycolate, aluminum hydroxide, aluminum sulfate, calcium sulfate or calcium hydroxide.

9. The hydrogel cooling patch according to claim 1, characterized in that: The cross-linking regulator is one or more of citric acid, lactic acid or succinic acid.

10. The method for preparing a hydrogel cooling patch according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh the raw materials of the hydrogel layer by weight percentage, mix CHOWDRUS CRISPUS, potassium chloride, calcium chloride, a thickener, a humectant, a preservative, a grapefruit capsule extract, denatonium benzoate, and pure water, and stir at a speed of 100-300 rpm until the mixture is uniform to obtain a hydrogel layer; S2. Weigh the raw materials of the matrix layer by weight percentage, mix sodium polyacrylate, chelating agent, humectant, crosslinking agent, crosslinking regulator, thickener, preservative, thermochromic microcapsule, pure water, and stir at 100-300rpm until the mixture is uniform to obtain a matrix layer; S3. The two hydrogel layers obtained in step S1 are respectively bonded to the upper and lower surfaces of the matrix layer obtained in step S2, and the hydrogel cooling patch is obtained after being allowed to stand for forming.

Citation Information

Patent Citations

  • Manufacturing method of sterile high-molecular hydrogel patch and sterile high-molecular hydrogel patch prepared by method

    CN114533704A

  • Method for preparing dietary fibers from wastes and byproducts generated in tangerine processing

    CN102805350A

  • Gel patch and preparation method thereof

    CN104546808A

  • Medical defervescence patch and preparation method thereof

    CN104688408A

  • Hydrogel wound dressing and preparation method and application thereof

    CN105536042A

Cited By

  • Organic microcapsule temperature control gel layer, hydrogel cooling patch and preparation method of hydrogel cooling patch

    CN120024097A